Avaliação das propriedades físico-químicas do óleo de pequi - Moreira, Melissa Claudino Dantas (Universidade Federal Rural do Semi-Árido, 2017)
The pequi (Caryocar brasiliense) is a fruit of high economic interest, because the oil obtained in it has applications in medicine, cosmetics and petrochemical industry. The objective of this work was to study the properties of pequi oil through its physicochemical characterization. The techniques used were density, humidity, viscosity, gas chromatography coupled to the mass spectrometer, besides the determinations of the acidity and saponification indexes. The oil used in this work was extracted from the pulp of pequi, whose extraction process was through cooking. The density analysis was performed according to ASTMD 4052. It was obtained value0.911569 g / cm³ as result at 20 ° C. The characterization of fatty acids and vitamins, performed by gas chromatography, the presented values similar to those found in the literature. Fatty acid composition data showed that the oil is very rich in oleic and palmitic acid, with the presence of vitamins B, C and E which are important for applications in various areas of industry.
Keywords: Óleo de Pequi; Pequi Oil; Cromatografia; Chromatography; Densidade; Density; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA